Presiden Wanita dalam Perspektif Media - Sadikin, Aning Sofyan (FIkom Unisba, 2008)
This controversy looks like never ending: Did Islam permitt a woman to become a president? Before SI 2001, the polemic of that problem still happened, even more strict. It is not strange if mass media gave bigger covering on that issue. This research tries to describe news covering on two ideological different national newspapers, Republika and Kompas, periode June until July 2001.